PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SISWA DI SDN 42 KORONG GADANG KECAMATAN KURANJI PADANG - Henico Putri Lina (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
School is one of the educational institutions that serve as targets Behavior Clean and HealthyLifestyle ( PHBs ). This is because the amount of data a disease that occurs in school-age children (ages6-10 ) such as intestinal worms ( 60–80 % ) , and dental caries ( 74 % ) . This study aimsto describeof PHBS students at 42elementary school Korong Gadang Kuranji District of Padang in 2014. Thisresearch is descriptive. Thepopulation was all students grades 4–6 elementary school who are 71and all the population sampled. Univariatble descriptive analysis to describe the characteristics ofthe respondent. The results showed that the knowledge was lowest for the use of sanitary latrines andhealthier, which amounted to 67.6 % , amounting to 56.3 % of students did not accept to be a healthysnack in the cafeteria sekolahdan as much as 100 % of students do not carry healthy snacks in the schoolcafeteria. This study suggests that schools can optimize the PHBs by activating the UKS program atthe school. This study suggests that schools can optimize the PHBs by activating the program of SchoolHealth UnitKeywords: behavio-r, students, 42 Elementary School Korong Gadang